Design and Fabrication of in-Wheel Suspension in Bicycle - Gowri Shankar M, Ajay S, Prasanna N and Rajagopal T (International Journal of Advanced Science and Technology, 2020)
Bicycle suspension is that the system accustomed comfort or sophisticate the rider and bicycle in order to insulate them from the roughness of the terrain. Bicycle suspension is employed totally on mountain bikes but is additionally common on commercial bicycles. Bicycles with the suspension at the front are known as hard tail and suspensions in the front and rear are known as dual or full suspension bikes. When a bicycle has no suspension the cycle is going to be rigid. Many manufacturers had tried other variations to the telescopic fork. for instance, Cannondale designed a shock build into the steerer tube called Head Shock.  The in-wheel suspension is one sort of suspension which has shock absorbers inside wheel rim at an angle to every other. The in-wheel suspension provides a suspension effect much greater than the traditional telescopic suspension in bicycles. The suspension is that the main component in every vehicle because it provides comfort for the driver and also the passengers. Though bicycles don‘t need much greater effects of suspension the in-wheel suspensions to absorb the strong vibrations on the vehicle. The in-wheel suspension is one of the emerging suspension concepts in the industry, especially in bicycle suspension. Value efficiency is another major impact of this technique. Providing the simplest and price-efficient suspension is that the main theme of the project.